Human Resources Competences in Economics Higher Education Provider in East Java, Indonesia : The determinant of organizational performances - Fariz, Fariz (APMBA (Asia Pacific Management and Business Application), 2019)
This study seeks to fill a gap (gap) is to integrate human resource competencies, and a culture of innovation in improving organizational performance and competitiveness, especially in the Economics Higher Education Institutes (STIE) in East Java.The study population was the whole STIE in East Java as it listed in LLDIKTI who has at least 50% of study program accredited "B from BAN PT (body of national accreditation) resulting 11 STIE. This study used a sample of saturated (census) on the grounds that the number of population in this study include small , Respondents from the entity unit examined in STIE institution is the Chairman, Vice Chairman I (Academic Affairs) and Chairman of the Program. with a total of as many as 49 (the Forty-Nine) man.Results of testing the hypothesis can be explained: Competence of human resources has a positive impact on organizational performance and exhibited significantly STIE. The results of this study indicate that the first hypothesis (H1) is accepted; Competence of human resources through a culture of innovation has a positive impact on organizational performance and exhibited significantly STIE These results indicate that the second hypothesis (H2) is received. Organizational performance and exhibited significantly have a positive effect on the competitiveness of STIE The results of this study indicate that the third hypothesis (H3) is received.